Coming in and Finding Out: Blending Receptor‐Targeted Delivery and Efficient Endosomal Escape in a Novel Bio‐Responsive siRNA Delivery System for Gene Knockdown in Pulmonary T Cells. Issue 7 (26th April 2019) - Kandil, Rima; Xie, Yuran; Heermann, Ralf; Isert, Lorenz; Jung, Kirsten; Mehta, Aditi; Merkel, Olivia M.
Abstract: RNA interference (RNAi) offers the potential to selectively silence disease‐related genes in defined cell subsets. Translation into the clinical routine is, however, still hampered by the lack of efficient carrier systems for therapeutic siRNA, endosomal entrapment presenting a major hurdle. A promising siRNA delivery system has previously been developed on the base of polyethylenimine (PEI) and the targeting ligand transferrin (Tf) to specifically reach activated T cells in the lung. In the present work, the focus is on optimizing Tf‐PEI polyplexes for gene knockdown in primary activated T cells by improving their endosomal escape properties. Blending of the conjugate with membrane lytic melittin significantly enhanced endosomal release and thereby cytoplasmic delivery, while maintaining selective T cell targeting abilities and overall cell tolerability. The gathered data furthermore demonstrate that melittin addition also distinctly improves several other essential particle characteristics, such as siRNA encapsulation efficiency and stability in lung lining fluids. In conclusion, this results in a novel upgraded siRNA delivery system that is not only able to specifically deliver its payload to the desired target cells via receptor‐mediated endocytosis, but also shows enhanced release from endosomal vesicles in order to initiate RNAi in the cytoplasm. Abstract : The blending of transferrin‐polyethylenimine with membrane lytic melittin results in a novel short interfering RNA (siRNA) delivery system combining targeting of activated T cells and efficient endosomal release properties. This carrier system displays optimal characteristics for pulmonary delivery of siRNA as a potential new therapy for inflammatory lung diseases such as asthma.